Direct Effects from the Implementation of the EU Energy and Climate Package on Cypriot Economic Sectors and Households - Shoukri, Elpida; Zachariadis, Theodoros (My University, 2011)
This report is a unified version of deliverables D6.1 and D.8 of the research project entitled “Economic Impacts from the Implementation of the European Union’s Energy and Climate Change Legislation Package in Cyprus”, which is funded by the Research Promotion Foundation of Cyprus in the framework of ‘DESMI 2009-2010’, a programme co-funded by the Republic of Cyprus and the European Regional Development Fund (project number ΑΕΙΦΟΡΙΑ/ΚΟΙΑΦ/0609(ΒΙΕ)/02). The report delineates the EU Energy and Climate package and presents the assessment of the effects from the implementation of this legislation on the various sectors of the Cypriot economy. It is necessary to assess at this stage the effects from the implementation of the legislation, in order to identify those economic sectors that are particularly prone to changes in production costs and consumer prices. This will enable performing realistic simulations of economic impacts by sector in the subsequent work packages of the project. The report summarises the provisions of the relevant EU legislation and provides an assessment of the direct economic effects by sector. These impacts have been assessed after extensive consultation with virtually all stakeholders from sectors of the economy of Cyprus that are expected to be affected by the energy and climate change legislation; details about the stakeholder consultation process are also provided.
Keywords: Cypriot Economic Sectors; Energy and Climate Package; Cypriot Households